Health Education In Improving The Self-Efficacy Management Of Hypertension Patients At Dr.Chalid Makassar Hospital - Sriwahyuni Sriwahyuni; Junaidin Junaidin; Samila Samila; Alfiah Alfiah; Sri Darmawan (International Journal of Health and Social Behavior, 2024)
Hypertension is a condition where blood pressure increases above normal, caused by various factors. The prevalence of hypertension in Indonesia among the population aged 18 years is 34.1%. Hypertensive patients must understand the importance of medication compliance so that effective communication between health care providers is needed.so that patients are able to self-efficacy MethodDescriptive research with cross sectional study subjects were hypertension patients with a sample of 43 people using a purposive sampling technique in accordance with inclusion criteria as secondary data and primary data in the form of a self-efficacy management questionnaire. Resultsafter health education was obtained, the Negative Ranks data showed that respondents' scores from pre-post 5 respondents experienced a decrease in self-efficacy management after health education, while the positive ranks data showed that 22 respondents' scores from pre-post experienced an increase in self-efficacy management after health education was carried out, and the data ties showed that 16 respondents got a fixed score from pre-post after health education, the Wilcoxon statistical test obtained a p value = (0.001) <α (0.05), then the alternative hypothesis (Ha) was accepted .Conclusion: There is an influence of health education on improving the self-efficacy management of hypertension sufferers at Dr. Chalid General Hospital Makassar. Suggestions for patients to be more active in seeking information in increasing self-efficacy in the treatment of hypertension.